СЛУЖБОВО-БОЙОВА ПІДГОТОВКА У ЗМІСТІ ПРОФЕСІЙНОЇ ОСВІТИ ПРАЦІВНИКІВ ПІДРОЗДІЛУ ПОЛІЦІЇ СПЕЦІАЛЬНОГО ПРИЗНАЧЕННЯ - Голенко, Ніна Миколаївна (SUPREMANCE OF LAW, 2017)
The article deals with studying the notion of the service-combative training during the professional education of policemen in the special subdivisions in the context of general education and special departmental legislation and the neighboring with it questions. Analyzing the components of the professional training of the law enforcement agencies of Ukraine in the retrospective and in the current legislation, a conclusion has been made as to possible implementation of certain despositions into the projects of normative acts having to reglamentate the procedure of the service-combative training of law enforcers from the special police. In the limits of a new educational legislation, the signs of the professional training of policemen of the corresponding subdivisions and their service-combative training as the preconditions of acquiring the corresponding competence are examined. Special attention is paid to the general and special competence of law enforcers of the special police from the point of view of the general and special legal prescriptions.
Keywords: special; subdivision; assignment; service-combative training; professional training; education